Probability, Uncertainty and Quantitative Risk - Peng, Shi-Ge
Probability, Uncertainty and Quantitative Risk is a high-quality, peer-reviewed, open-access journal reporting significant developments in modern probability theory, its relation to stochastic analysis and statistics, stochastic processes, their dynamics and control, as well as applications in domains such as finance, economics, biology, computer science, and the corresponding data analysis.